2014
DOI: 10.1242/jcs.156786
|View full text |Cite
|
Sign up to set email alerts
|

TRE17/USP6 regulates ubiquitination and trafficking of cargo proteins that enter cells by clathrin-independent endocytosis

Abstract: Plasma membrane proteins that enter cells by clathrin-independent endocytosis (CIE) are sorted either to lysosomes for degradation or recycled back to the plasma membrane. Expression of some MARCH E3 ubiquitin ligases promotes trafficking of CIE cargo proteins to lysosomes by ubiquitylating the proteins. Here, we show that co-expression of the ubiquitin-specific protease TRE17/USP6 counteracts the MARCH-dependent targeting of CIE cargo proteins, but not that of transferrin receptor, to lysosomes, leading to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 40 publications
(70 reference statements)
2
28
0
Order By: Relevance
“…However, a vital question that remained unanswered was the identity of USP6’s relevant substrates. Previous studies indicate that USP6 promotes both de-ubiquitination of itself and of clathrin-independent endocytic pathway cargoes in vivo (21), (22). However, it remained unknown whether any of these proteins are direct substrates of USP6, and what their relevance is to transformation.…”
Section: Introductionmentioning
confidence: 99%
“…However, a vital question that remained unanswered was the identity of USP6’s relevant substrates. Previous studies indicate that USP6 promotes both de-ubiquitination of itself and of clathrin-independent endocytic pathway cargoes in vivo (21), (22). However, it remained unknown whether any of these proteins are direct substrates of USP6, and what their relevance is to transformation.…”
Section: Introductionmentioning
confidence: 99%
“…USP6NL , ubiquitin specific peptidase 6 N-terminal like, has a role in the EGF receptor (EGFR) signaling pathway by acting as a GTPase-activating protein and inhibiting internalization of EGFR [27]. Insight for a role of USP6NL may be gained from information about USP6 which regulates ubiquitylation and trafficking of cargo protein by clathrin-independent endocytosis [28]. There is a growing body of evidence from studies in humans and mice supporting a role for clathrin-mediated endocytosis in AD [29-31] In addition, the association of the phosphatidylinositol binding clathrin assembly protein ( PICALM ) gene to AD is well established [12].…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, the entire coding sequence of USP6 is retained. USP6 functions in remodeling of the cytoskeleton and extracellular matrix, inflammatory response, cell signaling, cellular trafficking, and protein turnover, 23,27,[36][37][38][39][40][41][42][43][44] but its specific role in tumorigenesis is not entirely clear. More recently, Quick et al 45 reported that Jak1-STAT3 signaling has an essential role in USP6-related tumorigenesis, while Madan et al 46 suggested a role for Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%